2009
DOI: 10.1159/000262449
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biological Aging Process – A Population-Based Study of Healthy People in China

Abstract: Background: Although there have been cross-sectional and longitudinal studies examining biological age (BA) with chronological age (CA)-related changes in physical, physiological, biochemical, and hormonal variables, few studies have performed echocardiographic evaluation of the cardiovascular system and inflammatory biomarkers. Furthermore, little is known about biomarkers of aging and BA score (BAS) for healthy people in China. Objectives: The purpose of this study was to identify the biomarkers of healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…The biological age score has been suggested to be superior to chronological age in assessing cardiovascular variables in healthy aging (44). However, derivation of a similar biological score was beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 95%
“…The biological age score has been suggested to be superior to chronological age in assessing cardiovascular variables in healthy aging (44). However, derivation of a similar biological score was beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 95%
“…High CAVI values and high mean IMT are major risk factors for stroke [19,20]. It has also been reported that the CAVI, mean IMT, and cystatin C level increase with aging [21,22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…In early exploratory studies, the BA formulae of males and females were analyzed separately, and the sample size was usually small, which was often less than 100 people in most circumstances [7, 17, 18, 20, 21]. Then with the development of BA formula construction, the sample size was expanded accordingly [11, 12, 19, 2325]. Meanwhile, both males and females were comparably included, and the ratio of two genders was near to 1 : 1 in many studies, which may avoid the sexual factors caused by the gender differences of ageing process [11, 12, 2225].…”
Section: Criteria Of Subject Enrollmentmentioning
confidence: 99%
“…Then with the development of BA formula construction, the sample size was expanded accordingly [11, 12, 19, 2325]. Meanwhile, both males and females were comparably included, and the ratio of two genders was near to 1 : 1 in many studies, which may avoid the sexual factors caused by the gender differences of ageing process [11, 12, 2225]. The expanding sample size and balanced ratio of two genders are required to give deeper view of BA in the whole population.…”
Section: Criteria Of Subject Enrollmentmentioning
confidence: 99%
See 1 more Smart Citation